A comparison of yield curve estimation techniques using UK data - Ioannides, Michalis (Journal of Banking & Finance, 2003)
I compare different methods of estimating the term structure of interest rates on a daily UK treasury bill and gilt data that spans the period from January 1995 to January 1999. In-sample and out-of-sample statistics reveal the superior pricing ability of certain methods characterised by an exponential functional form. In addition to these standard goodness of fit statistics, model performance is judged in terms of two trading strategies based on model residuals. Both strategies reveal that parsimonious representations of the term structure perform better than their spline counterparts characterised by a linear functional form. This is valid even when abnormal returns are adjusted for market movements. Linear splines overfit the data and are likely to give misleading results.